Insulation and body temperature changes by wearing a thermal swimsuit during low to moderate intensity water exercise - Wakabayashi, H.; Kaneda, K.; Hanai, A.; Yokoyama, S.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
This study investigated thermal swimsuit (TSS) effects on body temperature and thermal insulation during low-intensity and moderate-intensity water exercise. Nine male subjects were immersed in water (23°C) and pedalled on an underwater ergometer for 30 min with a TSS or a normal swimsuit (NSS) at two exercise intensities. Oesophageal temperatures CTCS) were maintained higher in TSS than in NSS at both intensities. Moderate exercise decreased the tissue insulation (Itissue) compared to low-intensity exercise. However, the increased metabolic heat production at moderate intensity and added suit insulation (Isuit) were sufficient to offset the decrement of Itissue and Tes. The proportion of Isuit to total insulation and skin-fold thickness showed a negative correlation, indicating that subjects with lower body fat can benefit more from wearing TSS. Results suggest that TSS in cool water was especially useful for subjects with low body fat.